Management of Colonic Volvulus - Gingold, Daniel; Murrell, Zuri (Clinics in Colon and Rectal Surgery, 2012)
Colonic volvulus is a common cause of large bowel obstruction worldwide. It can affect all parts of the colon, but most commonly occurs in the sigmoid and cecal areas. This disease has been described for centuries, and was studied by Hippocrates himself. Currently, colonic volvulus is the third most common cause of large bowel obstruction worldwide, and is responsible for ∼15% of large bowel obstructions in the United States. This article will discuss the history of colonic volvulus, and the predisposing factors that lead to this disease. Moreover, the epidemiology and diagnosis of each type of colonic volvulus, along with the various treatment options will be reviewed.
Keywords: volvulus; decompression; resection; cecopexy; fixation